2018
DOI: 10.1177/0194599818764627
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Human Nasal Inferior Turbinate–Derived Mesenchymal Stem Cells to Repair Vocal Fold Injuries

Abstract: Objective This study investigated the ability of implanted human nasal inferior turbinate-derived mesenchymal stem cells (hTMSCs) to repair injured vocal folds. To this end, we used quantitative real-time polymerase chain reaction (PCR) to analyze the early phase of wound healing and histopathological analysis to explore the late phase of wound healing in xenograft animal models. Study Design Prospective animal study. Setting Research laboratory. Subjects and Methods The right-side lamina propria of the vocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Previous studies have verified that hTMSC exhibits the properties of MSC and hTMSC has been used in regenerative medicine in a variety of contexts . In the field of vocal fold regeneration, hTMSC has exhibited antifibrotic effects in both qPCR and histologic examination …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies have verified that hTMSC exhibits the properties of MSC and hTMSC has been used in regenerative medicine in a variety of contexts . In the field of vocal fold regeneration, hTMSC has exhibited antifibrotic effects in both qPCR and histologic examination …”
Section: Discussionmentioning
confidence: 89%
“…A previous study revealed that the survival period of hTMSC transplanted to injured vocal folds was more than 2 weeks but not more than 1 month . Therefore, transplanted stem cells are believed to exhibit a paracrine effect continuously for at least 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrastriatal administration of hTMSCs at 1 day after MCAo could provide comparable motor functional recoveries in 2 different neurologic examinations compared to AdMSCs, demonstrating outstanding therapeutic potentials of hTMSCs against ischemic stroke. Moreover, another study reported that hTMSCs could repair vocal fold injuries by promoting growth factors and extracellular matrix materials, supporting the excellent regenerative capabilities of hTMSCs [ 17 ]. As both hTMSCs isolated from hypertrophic and contralateral normal inferior turbinate showed indistinguishable characteristics of stem cells [ 13 ], hTMSCs we utilized in the present study are basically not pathologic, alleviating possible safety issues.…”
Section: Discussionmentioning
confidence: 92%